Development and Characterization of Sugar Palm (Arenga Pinnata (Wurmb. Merr)) Fiber Reinforced Cassava (Manihot esculenta) Starch Biopolymer Composites - Mousa S.A.; Sapuan S.M.; Harussani M.M.; Jamal T.; Azri M.A.M.; Ilyas R.A.; Azman M.A.; Siddiqui V.U.; Rafin T. (Taylor and Francis Ltd., 2024)
The study aims to develop a biopolymer composite made of sugar palm fiber and cassava starch that may degrade over time and to investigate the physical and structural characteristics of biocomposite films. Sugar palm fiber (SPF) was cast into a biocomposite with cassava starch (CS) as the matrix and fructose as the plasticizer using the casting process. The thermoplastic CS composite sheet was loaded with different amounts of SPF (0%, 5%, 10%, 15%, and 20% dry starch). The addition of SPF considerably improved the physical and thermal properties. It enhanced the thickness of the material while lowering its density, water content, and biodegradability. However, there was no significant increase in the tensile properties of the composite films. The filler had been absorbed into the matrix, according to SEM micrographs. With a higher concentration of SPF, the SPF/CS films had a more heterogeneous surface. It is indeed possible that the addition of SPF changed the film characteristics of cassava starch, potentially compromising the performance of the films. Overall, the findings of this study concentrate on enlightening about biopolymer composite film and highlighting its great potential for the food packaging market. 2023 The Author(s). Published with license by Taylor & Francis Group, LLC.